Estimulando o pensamento computacional no ensino médio utilizando o software Scratch - Pinho, Robério Girão (2024)
This study investigates the use of Scratch as a tool for teaching programming and developing Computational Thinking among first-year high school students in a vocational school. The research aimed to identify the students’ prior knowledge of computing, evaluate their satisfaction with using Scratch, and analyze the impact of the tool on the development of logical reasoning and creativity. Through a structured course with progressive challenges and the creation of a personal project, students were introduced to basic programming concepts in a playful and visual manner. Data were collected through questionnaires that explored students’ profiles, their prior experiences with computing, and their perceptions of the programming experience provided by the classes. The results showed that Scratch proved to be an effective tool for learning programming, even for students with limited prior knowledge in computing. Most students reported high satisfaction with the tool and observed significant development in their logical reasoning and problem-solving skills, which are fundamental to Computational Thinking. Additionally, the proposed challenges contributed to student engagement and the creation of increasingly complex projects. Although Scratch was shown to be an effective tool for teaching programming, some concepts, such as control structures, required more time to be fully understood by students, necessitating adjustments in the initial course planning. The methodology used in this study can serve as a basis for implementing similar projects in other schools, contributing to the democratization of access to programming education and the development of essential 21st-century skills